2008
DOI: 10.1146/annurev.psych.58.110405.085650
|View full text |Cite
|
Sign up to set email alerts
|

Social Bonds and Posttraumatic Stress Disorder

Abstract: Retrospective and prospective studies consistently show that individuals exposed to human-generated traumatic events carry a higher risk of developing Posttraumatic Stress Disorder (PTSD) than those exposed to other kinds of events. These studies also consistently identify perceptions of social support both before and after a traumatic event as an important factor in the determining vulnerability to the development of PTSD. We review the literature on interpersonal traumas, social support and risk for PTSD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
491
3
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 771 publications
(540 citation statements)
references
References 153 publications
(136 reference statements)
39
491
3
7
Order By: Relevance
“…For example, a study of women's worst hotspots during birth (defined as of peak emotional distress) found that over a third of hotspots were due to interpersonal factors such as feeling abandoned, being ignored and lacking support (Harris & Ayers, 2012) . Similarly, in the PTSD literature there is evidence that interpersonal traumas where a person is perceived as the perpetrator are more likely to result in PTSD (Charuvastra & Cloitre, 2008). Conversely, there is evidence from experimental studies using birth stories that positive support may be critical in improving women's perceived control and reducing perceived trauma .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of women's worst hotspots during birth (defined as of peak emotional distress) found that over a third of hotspots were due to interpersonal factors such as feeling abandoned, being ignored and lacking support (Harris & Ayers, 2012) . Similarly, in the PTSD literature there is evidence that interpersonal traumas where a person is perceived as the perpetrator are more likely to result in PTSD (Charuvastra & Cloitre, 2008). Conversely, there is evidence from experimental studies using birth stories that positive support may be critical in improving women's perceived control and reducing perceived trauma .…”
Section: Discussionmentioning
confidence: 99%
“…Among the well-known risk factors or covariates of posttraumatic stress are high severity of exposure (Santiago et al, 2013), being female (Olff, Langeland, Draijer, & Gersons, 2007), low levels of social support (Charuvastra & Cloitre, 2008; Ozer, Best, Lipsey, & Weiss, 2003), and high neuroticism (Ormel et al, 2013). Despite the numerous studies that have investigated these factors as predictors of posttraumatic stress, few have examined why or how they lead to the development of posttraumatic stress symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…Other women may have a seemingly "normal" birth but may feel traumatized by aspects such as loss of control, loss of dignity, or the hostile, difficult or disrespectful attitudes of the people around them. The interpersonal environment during birth may be particularly important in determining trauma responses (Charuvastra & Cloitre, 2008;Cigoli, Gilli, & Saita, 2006;Creedy et al, 2000;Czarnocka & Slade, 2000;Ford & Ayers, 2009;Lyons, 1998;Maggioni et al, 2006;Soet et al, 2003;Wijma, Soderquist, & Wijma, 1997).…”
Section: Introductionmentioning
confidence: 99%